Design, synthesis, in vitro, and in silico studies of 1,2,4-triazole-piperazine hybrid derivatives as potential MAO inhibitors - Uslu, Harun; Osmaniye, Derya; Saglik, Begum Nurpelin; Levent, Serkan; Ozkay, Yusuf; Benkli, Kadriye; Kaplancikli, Zafer Asim (Academic Press Inc Elsevier Science, 2021)
Monoamine oxidases (MAOs) have become promising drug targets for the development of central nervous system agents. In recent research, it was shown that numerous piperazine derivatives exhibit hMAO inhibitory activity. Therefore, in this study, a novel series of 1,2,4-triazole-piperazine derivatives (5a-j) were designed, synthesized, characterized, and screened for their hMAO-A and hMAO-B inhibitory activities. When the ADME predictions were examined, it was seen that the pharmacokinetic profiles of all synthesized compounds were appropriate. Compounds 5a, 5b, 5c, and 5e, with H, F, Cl, and NO2 groups on the 4-position of the phenyl ring, respectively, showed important MAO-A inhibitory activity. Compound 5c was found to be the most effective agent among the synthesized compounds with an IC50 value of 0.070 +/- 0.002 mu M against the MAO-A enzyme. The synthesized compounds appear to support the results of other studies to design MAO inhibitors to obtain more suitable drugs, especially for neurological disorders such as depression and anxiety.
Keywords: hMAO enzymes; Enzyme inhibition; Triazole; Piperazine; ADME; Molecular Docking